Online Marketing Effects: Social Media Engagement in Promoting Batik among MSMEs - Prihatining Wilujeng, Ita; Fitri, Raisa; Dian Wahyudi, Handri; Ratna Sungkar, Alifia; Lestari Wahyuningtyas, Dea (Dinasti International Journal of Management Science, 2024)
The batik industry, which MSMEs dominate, is one of Indonesia's strengths of cultural heritage and economic growth. The development of technology and information has changed business processes, one of which is the marketing process to become completely digital. Selling via social media has opened up opportunities for some MSMEs in the batik industry, a potential industry in Indonesia, to market their products by targeting consumers of various ages and social statuses. This research aims to understand the effectiveness of social media marketing and consumer engagement with sellers through social media marketing. This research will provide insight for MSMEs in the batik industry to optimize their marketing strategies through social media engagement. This research uses a triangulation method by combining the results of interviews with batik entrepreneurs, consumers of batik products, and theory. Analysis of interview results reveals that young consumers feel that selling batik via social media is very effective and is their primary choice. Batik entrepreneurs in Banyuwangi feel that promotions through online social media and offline promotions through physical stores, festivals, and exhibitions are equally important promotional media for attracting customers from various groups. The current analysis highlights excellent and effective social media promotion strategies for batik entrepreneurs in Banyuwangi to increase consumer engagement and desire to buy products.